Proposed update to the taxonomy of the genera Hepacivirus and Pegivirus within the Flaviviridae family - Smith, Donald B. (J Gen Virol, 2016)
Proposals are described for the assignment of recently reported viruses, infecting rodents, bats and other mammalian species, to new species within the Hepacivirus and Pegivirus genera (family Flaviviridae). Assignments into 14 Hepacivirus species (Hepacivirus A–N) and 11 Pegivirus species (Pegivirus A–K) are based on phylogenetic relationships and sequence distances between conserved regions extracted from complete coding sequences for members of each proposed taxon. We propose that the species Hepatitis C virus is renamed Hepacivirus C in order to acknowledge its unique historical position and so as to minimize confusion. Despite the newly documented genetic diversity of hepaciviruses and pegiviruses, members of these genera remain phylogenetically distinct, and differ in hepatotropism and the possession of a basic core protein; pegiviruses in general lack these features. However, other characteristics that were originally used to support their division into separate genera are no longer definitive; there is overlap between the two genera in the type of internal ribosomal entry site and the presence of miR-122 sites in the 5′ UTR, the predicted number of N-linked glycosylation sites in the envelope E1 and E2 proteins, the presence of poly U tracts in the 3′ UTR and the propensity of viruses to establish a persistent infection. While all classified hepaciviruses and pegiviruses have mammalian hosts, the recent description of a hepaci-/pegi-like virus from a shark and the likely existence of further homologues in other non-mammalian species indicate that further species or genera remain to be defined in the future.